Effectiveness of hand-arm bimanual intensive therapy including lower extremities in the rehabilitation of children with cerebral palsy: a systematic review protocol - Daniela Ebner-Karestinos; Rodrigo Araneda; Asfarina Zanudin; Ya-Lan Qu; Dzalani Harun; Siaw Chui Chai (BMJ Open)
Introduction Cerebral palsy (CP) is a paediatric disorder with permanent impairment of movement and posture with a prevalence of about 2.11 in 1000 births in the world. Given the therapeutic effect of hand-arm bimanual intensive therapy including lower extremities (HABIT-ILE) in children with CP, a systematic review of the available literature on this topic is warranted. The objective of this study is to systematically review the effectiveness of HABIT-ILE on upper extremity, lower extremity and trunk outcomes within the domains of body functions and structures, activity and participation of the International Classification of Functioning, Disability and Health in children with CP.Methods and analysis This study will be conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Searches will be conducted in six databases: MEDLINE, PubMed, Cochrane Library, Scopus, OT seeker and Web of Science for available published literature. The grey literature sources will include WorldCat, National Technical Information Service, Agency for Healthcare Research and Quality, Open Grey, WHO and OpenDOAR. Manual searches of citations of included papers will be performed to collect all experimental studies of HABIT-ILE in children with CP. The level of evidence for included articles will be classified according to the level of evidence in the guidelines for systematic reviews on the American Occupational Therapy Association website. Based on the study design of the included articles, the risk of bias will be assessed using the revised Cochrane risk-of-bias tool, the Cochrane Risk Of Bias In Non-randomised Studies – of Interventions tool and the quality assessment tool recommended by the American Occupational Therapy Association. In order to synthesise the data, narrative synthesis will be used, along with meta-analysis, if available.Ethics and dissemination As this study only reviewed previously published articles, ethical approval was not required. The findings will be published in a peer-reviewed scientific journal.PROSPERO registration number CRD42024518179.